Faktor-Faktor yang Mempengaruhi Konsumen Belanja di Pamella Yogyakarta - Yuana Tri Utomo; Abdi Mujahidin Rahim; Hery Sasono (Journal of Trends Economics and Accounting Research, 2023)
Consumer behavior is an activity or action taken by consumers before making a purchase of products or services in meeting their needs which can be influenced by various factors. This study aims to determine the factors that influence consumers to shop at Pamella Supermarket. This study used a quantitative approach. The data collection techniques used were interviews and questionnaires. The sample in this study amounted to 100 respondents who shopped at Pamella Supermarket. The results of this study show that the factors that influence consumers to shop at Pamella Supermarket are divided into 6 factors, namely: convenience factors, cultural factors, consumer resource factors, consumer knowledge factors, company reputation factors, and motivation factors.